Histories of human engineering : tact and technology - Derksen, Maarten (Cambridge : Cambridge University Press, 2017)
This fascinating account of the histories of human engineering, from brainwashing and mind control to Dale Carnegie's art of dealing with people, reveals the perpetual tension between the desire to control people's behaviour and the resistance this provokes. Derksen shows that human engineering only works when applied with tact.
Includes bibliographies and index.
Keywords: Psychology; Philosophy; Social technology